Influência da potência de laser Nd: YAG na soldagem do aço inoxidável duplex UNS S32205 - Crespo, Gillian da Silva [UNESP] (2014)
We carried out a study of laser welding provided bead on plate in duplex stainless steel UNS S 32205 in the form of plates with 3,0 x 20 x 45 mm (H x W x D). 12 welds was performed in argon gas flow of 15 l/min, beam diameter 0,2 mm, angle of 90°, repetition rate of 9 Hz, welding speed of 150 mm / min, gas depths focus equal to 1,0; 1,5 and 2,0 mm below the surface of the workpiece and the pulse energy (Ep) set at 6,0 J. The power variation was obtained by varying the time width (Lt) at values of 4, 6, 8 and 10 ms. The results were analyzed based on the relationship between power, weld bead geometry, balance ferrite/austenite phases, Vickers hardness and chemical analysis. For structure revelation of the weld metals used both Behara modified and electrolyte with 10% oxalic solution reagents. Measures of geometry (width and depth) of the weld beads were made using images taken by digital camera on an ordinary optical microscope. Image processing was performed using the Image J program, a graphics editing software in the public domain lined on Java platform. The highest values of width and depth were found in higher values of power and increasing the value of the focal position resulted in an increase in the variability of the mean of these geometrical parameters. The balance sheet value of the ferrite/austenite for the base metal and weld metal was 52/48 % and 70/30% respectively. The average hardness for the base metal was equal to 286 HV. In weld metals and the ZTAs focal position -1.5 mm had the lowest hardness values, regardless of power used. The chemical composition of alloying elements did not show large variations between factory data and those obtained for the base metal and the weld metal